(untitled) (Research, Society and Development, 2021)
Objective: The present study aimed to demonstrate the relationship between Impostor Syndrome and Burnout Syndrome in the context of study and professional performance in the area of ​​Nursing. Methodology: For this purpose, a descriptive study was carried out, with a quantitative and correlational character, in which 106 people participated, being these Nursing students (60.4%) and Nursing professionals (39.6%). These responded to the Maslach Burnout Inventory and Clance Imposter Phenomenon Scale. Results: As a result, it was found that the participants had higher mean scores for the Burnout Syndrome compared to the Impostor Syndrome. In addition, there were positive and significant correlations between the general factor of the Impostor Syndrome and the factors depersonalization (r = .57; p < .01) and emotional exhaustion (r = .44; p < .01), characteristic of the Burnout Syndrome, as well as with the general Burnout factor (r = .51; p < .01). Conclusion: It is argued that the syndromes investigated in this study have significant implications for the physical and mental health of individuals and their well-being in general. It is hoped that the results obtained will direct new investigations on the theme and, later, support the development of intervention strategies to Burnout and Impostor Syndromes in the context of professionals working in health.